Characterization of un-17, chol-3 and chol-4, phospholipid biosynthetic mutants of Neurospora crassa - M Tanrikulu (Fungal Genetics Reports, 2000)
Four choline-requiring mutants of Neurospora crassa have been identified genetically. The chol-1 and chol-2 mutants are impaired in phosphatidylcholine biosynthesis. Phospholipid synthesis is also impaired in the inl and un-17 mutants; the inl mutant cannot synthesize inositol phospholipids. Defects in phospholipid biosynthesis are reported here for three previously uncharacterized mutants, un-17, chol-3 and chol-4.